Estimation of Photosynthetically Active Radiation Using Cropgro-Soybean Model - de Oliveira, Evandro Chaves; Roberti, Débora R.; da Costa, José Maria N.; Ferreira, Williams P. M.; Justino, Flavio B.; Rodrigues, Rafael A.; Neves, Leonardo de O.; Gonçalves, Paulo H. L.; Aguiar, Leonardo José G.; Moraes, Osvaldo L. L. (Ciência e Natura, 2011)
.